Modulation optimization effect on total harmonic distortion of single phase H-bridge inverter based selective harmonics E limination technique - Aboadla, Ezzidin Hassan Elmabrouk; Khan, Sheroz; Habaebi, Mohamed Hadi; Gunawan, Teddy Surya; Hamida, Belal Ahmed; Tohtayong, Majdee (IEEE, 2016)
Specific odd harmonics can be mitigated by operating the simeconductor switches in H-bridge inverters at optimized switching angles of the PWM signals. These switching angles can be achieved by calculating a set of nonlinear equations using Selective Harmonic Elimination Pulse Width Modulation (SHE PWM) technique. Modulation index (m) is a significant parameter used to control the amplitude of the fundamental output voltage of DC-AC inverter. By changing the value of modulation index the Total Harmonics Distortion (THD) also will change. In this paper, the influence of varying modulation index on the THD, and the performance of Hbridge inverter using SHE PWM scheme is evaluated. To investigate the effect different conditions of modulation index and different number of nonlinear equations to calculate the switching angles to achieve a minimum THD, single phase H-bridge inverter is simulated in Matlab-Simulink.